Expression of colSR Genes Increased in the rpf Mutants of Xanthomonas oryzae pv. oryzae KACC10859 - Noh, Young-Hee (Korean Society of Plant Pathology, 2014)
The rpf genes and colS(XOO1207)/colR(XOO1208) were known to require for virulence of Xanthomonas oryzae pv. oryzae (Xoo). In Xoo KACC10331 genome, two more colS/colR genes, colS(XOO3534) (raxH)/colR(XOO3535) (raxR) and colS(XOO3762)/colR(XOO3763) were annotated. The colS(XOO3534)/colR(XOO3535) were known to control AvrXa21 activity and functions of colS(XOO3762)/colR(XOO3763) were unknown in Xoo. To characterize the relationship between rpf and colS/colR genes, expression of colS/colR genes in Rpf mutants of Xoo were analyzed with quantitative reverse transcription PCR (qRT-PCR). Expressions of all three colS/colR genes increased in the rpfF mutant in which DSF synthesis is defective. Expression of colS(XOO1207)/colR(XOO1208), colS(XOO3534)/colR(XOO3535) and colS(XOO3762)/colR(XOO3763) increased 2, 2–7, 3–13 folds respectively. Expression of colS(XOO3534) and colS(XOO3762) also increased 2–4 folds in the rpfG mutant in which the signal from DSF is no longer transferred to down-stream. Expression of the other colS/colR genes was not significantly changed in the rpfG mutant compared to the wild type. Since RpfF and RpfG are responsible for DSF synthesis and signal transfer from DSF to down-stream to regulate virulence gene expression, these results suggest that the DSF and DSF-mediated signal regulate negatively three colS/colR genes in Xoo.